Analysis and evaluation of the achievement of strategic planning goals in the public sector (Journal of Economic Research & Business Administration, 2021)
The article analyzes the system of state planning in Kazakhstan. The analysis and evaluation ofthe achievement of goals and target indicators in the strategic documents of the central state and localexecutive bodies is carried out. The analysis is based on studies of international organizations, reportsof state bodies on strategic plans and programs for the development of territories, analytical reports ofthe Center for Research, Analysis and Evaluation of the Effectiveness of the Accounts Committee of theRepublic of Kazakhstan. The standards and best practices of the Organization for Economic Cooperationand Development (hereinafter – the OECD) used by the governments of developed countries in thedevelopment of strategic documents and standards were considered. The main problem areas for thedevelopment of strategic documents by the state bodies of the country are indicated. The article concludesthat the quality of strategic planning documents largely depends on the quality of predictive andanalytical work and on the methodological tools that are available to government agencies. The authorsalso come to the conclusion that strategic documents should be focused on solving current problems ofsociety, they should clearly observe the principle of decomposition of goals, and when developing them,alternative solutions to the problems that these documents are aimed at should be considered in orderto ensure the choice of the best and most effective solutions available to society.Key words: strategic planning, strategic goals, target indicators, analysis, evaluation, governmentagencies.